Model Kepercayaan Konsumen Pada Situs e-Commerce - Wika Purbasari (LPPM STMIK Widya Utama, 2017)
The world trading system has now grown to online commerce (electronic commerce) because a lot of people who buy goods through e-commerce. This can be evidenced by a study Consumer Web Watch reported that 86% of Internet users have switched make purchases traditional to online purchases, because that's important to know what factors are forming a model of consumer confidence in e-commerce, then it is necessary a prediction to determine any factors that shape consumer confidence in e-commerce. Methods in meta analysis of studies in the form of meta data with the Systematic Literature Review (SLR) used for identifying, assessing and analyzing primary research to investigate research questions in the search for variables that influence consumer confidence in e-commerce.